Multicomponent Solids of Niflumic and Mefenamic Acids Based on Acid-Pyridine Synthon - Kumar, Vineet; Goswami, Pramod Kumar; Balendra,; Tewari, Shailabh; Ramanan, Arunachalam (Frontiers in Chemistry, 2022)
The present study discusses comparative structural features of fourteen multicomponent solids of two non-steroidal anti-inflammatory drugs, Niflumic and Mefenamic acids, with amine and pyridine-based coformers. All the solids were structurally characterized through PXRD, SCXRD, DSC, and the monophasic nature of some of the solids was established through Rietveld refinement. The solid forms include salt, cocrystal, hydrate, and solvate. Except for two, all the solids reported here showed relatively higher solubility compared to the acids. The difference in pKa and similarity in structural features of both the molecules enabled us to study the effect of ΔpKa on crystallization outcome systematically. The structures of all the solids are described through acid-pyridine synthon perspective.